Sedation and general anesthesia for patients with Cornelia De Lange syndrome: A case series. Issue 2 (4th May 2016) - Moretto, Alessandra; Scaravilli, Vittorio; Ciceri, Valentina; Bosatra, Mariagrazia; Giannatelli, Federica; Ateniese, Bianca; Mariani, Milena; Cereda, Anna; Sosio, Simone; Zanella, Alberto; Pesenti, Antonio; Selicorni, Angelo
Abstract : Cornelia De Lange syndrome (CdLS) is a rare congenital disease characterized by typical facial dysmorphism, developmental disability, and limb deficiency defects. Various congenital malformations and medical complications have been described with gastroesophageal reflux as the major one. CdLS patients often require multiple high‐risk anesthetic procedures. At San Gerardo Hospital (Monza, Italy) the management of CdLS patients is routinely organized through a standard protocol and a dedicated pediatric anesthesia team has been implemented. We report on a retrospective descriptive analysis of the anesthetic records of the CdLS patients admitted to San Gerardo Hospital from January 2010 to December 2015. We retrieved: demographics, genetic profiles, type of procedures, anesthetic approaches, anesthetics usage and complications. Data are reported as median (interquartile range) values. Twenty‐seven patients (11 female), with age 12 (7–15) years old, weight 24 (14–35) kg, and severity score of 25 (18–32) were included. NIBPL mutations were the most frequently represented. We analyzed 58 procedures (30 esophagogastroduodenoscopies, 8 evoked auditory potential tests, 5 radiodiagnostics, 5 catheters positioning, 4 bronchoscopies) managed by sedation (36) and general anesthesia (6). Each patient underwent one (1–2) anesthetic procedure. Propofol (59%), sevoflurane (31%), fentanyl (24%), and ketamine (10%) were used. Three out of six endotracheal intubations were difficult. The only documented intraoperative complications were three episodes of desaturation (oxygen saturation <90%) occurring during sedations and were managed without the need for an invasive control of the airways. Implementation of a specific management protocol and a dedicated allowed to provide anesthesia to CdLS patients without the occurrence of major complications. © 2016 Wiley Periodicals, Inc.